Maintaining carbon stocks in extractive reserves in Brazilian Amazonia - Fearnside, Philip Martin; Nogueira, Euler Melo; Yanai, Aurora Miho (Desenvolvimento e Meio Ambiente, 2018)
Extractive reserves in the Amazon Forest maintain carbon stocks out of the atmosphere, thereby avoiding greenhouse-gas emissions that provoke global warming. This and other environmental services, such as recycling water and maintaining biodiversity, provide major reasons for creating these reserves and for according them priority in government programs. The importance of reducing carbon emissions from deforestation has been the principal motivation for international funding, which has been key to creating and supporting extractive reserves, notably in the cases of Germany through the PPG7 program and Norway through the Amazon Fund. Estimating the amount of carbon in these reserves and the losses that have occurred from deforestation is essential as an input to making decisions that affect current and potential future extractive reserves. By 2014, there were 47 federal extractive reserves in Brazil’s Legal Amazonia region, of which 45 were in the Amazonian Tropical Forest Biome and 26 extractive reserves belonged to states, all of which were in the Amazonia Biome. This study provides data for each of the 73 extractive reserves in Legal Amazonia, based on biomass information by forest type calculated from RadamBrasil survey data, and deforestation from PRODES monitoring by LANDSAT or equivalent satellites (30-m resolution). The stocks represent carbon in the “pre-modern” biomass, that is, the biomass present in approximately 1970, or before substantial deforestation or logging activity in the region. The carbon losses reflect only deforestation, not degradation of forest by logging and/or fire. The total area of extractive reserves in Legal Amazonia amounted to 126,709 km2, of which 4301 km2 (3.4%) had been cleared by 2014. Those extractive reserves had a remaining carbon stock in forest vegetation (above and below-ground) of 2.1 billion tons. The carbon lost to deforestation totaled 74.9 million tons. Avoiding further carbon loss to both deforestation and degradation needs to be a high priority for the extractivists, as it is the value of the forest’s environmental services that has the greatest potential for providing a means of support that is increasing in value and is inherently sustainable.